The Monstrous Feminine: Politics of Gender and Fear in the Adaptation of “Tejeemola” in Kothanodi - Sruthi B Guptha; Sandhya V (IAFOR Journal of Literature & Librarianship, 2023)
Contemporary folklore studies transcend genre, language, culture, time, and space in addressing the pertinent questions of representation, appropriation, and counter-cultures. This paper attempts to address gender politics in the formulation of horror in the visual adaptation of the famous Assamese folktale “Tejeemola” (1911) in Bhaskar Hazarika’s film Kothanodi (The River of Fables, 2015). The interval of almost a century makes Kothanodi undisputedly informed by contemporary postmodern discourses on femininity, sexuality, and socio-cultural changes in the conventions of gender. The retelling utilizes the trope of motherhood in the construction of the monstrous feminine to evoke fear. The paper looks critically at a) the cultural implications of fear in the visual adaptation by interrogating the monstrous feminine against the cultural glorification and romanticization of the maternal feminine, and b) how fear is used as a culturally rooted gendered tool in the language of cinema, drawing from Scruton’s Sociophobics: The Anthropology of Fear. The objective of this critical analysis is to recognize the fragile and fluid borders which shape our idea of fear and disassociate it from the intricate web of cultural conditioning.